Lifestyle Without Tobacco: Impact Of Health Education On Clean and Healthy Living Behaviorelementary School - Akram Akram; Hadi Pajarianto; Nurwahidin Hakim; Andi Sitti Umrah; Sri Rahayu Amri; Nur Saqinah Galugu (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2022)
Clean and Healthy Living Behavior (PHBS) is fundamental to be instilled in children from an early age because it protects them from various diseases. One form of protection that can be given, especially for school children, is protection against diseases caused by smoking behavior. Education has been an essential part of promoting health and preventing disease throughout the ages. Health education teaches physical, mental, emotional, and social health to develop knowledge, skills, and positive attitudes about health. This study aims to analyze the impact of health education on PHBS in elementary schools for areas that apply a tobacco-free lifestyle. The research method uses collaborative quantitative research with a cross-sectional observational approach. The population and samples were students in Bone-Bone Village Elementary School as a tobacco-free lifestyle area and Salukanan Village as a control village. The number of samples used in this study was 52 people. The data was then analyzed using the Pearson correlation test. The results showed that the health education provided by the Physical Health Education (PJOK) teachers to PHBS in schools was higher in Bone-Bone Village as many as 26 people (50%) while in Salukanan Village, as many as (30.8%). The results of the Pearson correlation test obtained a value = 0.00 and a correlation value (r) = 1,000, so it can be stated that health education provided by PJOK teachers has a powerful impact on children's PHBS in schools, especially in areas that apply a tobacco-free lifestyle